PRODUKTIFITAS PENGELOLAAN WAKAF DI KECAMATAN LICIN KABUPATEN BANYUWANGI - Ahmad Khoirin Andi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2019)
Wahbah Zuhaili said that Syari’ah principles is to realize the purpose of generation actually in creating happiness of individual and jama’ah, carrying out and cele brating the world with an infrastructures wich will present to proccess of the perfectness, kindness, wifure and civiitation. The purpose of reserch is to know on how the productivity practice in managing wakaf wealth in Licin Sub district, Banyuwangi Regency.